STUDI LITERATUR: PENGARUH SPIRITUAL CARE PADA PASIEN COVID-19 DI RUMAH SAKIT - Nurwahida, Nurwahida (Jurnal Keperawatan Profesional, 2022)
Spiritual care for Covid-19 patients involves the dynamic dimension of human life related to the way they are connected in the moment, with God, themselves, others and nature. Spiritual care has an important role in minimizing the psychological impact experienced by Covid-19 patients. Objective: to determine the effect of providing spiritual care interventions by nurses in the nursing care process when patients undergo hospitalization. Methods: database searches include Google Scholar, Science Direct, and Elsevier with keywords spiritual approach, CoronaVirus Disease patient, spiritual care, Covid-19 Patient. The inclusion criteria used by the author is to limit articles or journals published in the last five years starting from 2017 to 2021. Results: Analysis of 15 articles found that CoronaVirus Disease (Covid-19) patients undergoing hospitalization experienced improved mental health and receive support through a spiritual approach (Spiritual care). Conclusion: Spiritual care can effectively stimulate the coping of Covid-19 patients who are being treated in hospitals in improving their mental health, this has a positive impact on increasing the body's immunity of Covid-19 patients and changes in healthy behavior as an indicator of adaptive coping mechanisms.